A Rapid Gas Chromatography Method For Simultaneous Determination Of Lpg Compounds - Nofrizal Nofrizal; Lisna Rosmayati; Yayun Andriani (Scientific Contributions Oil and Gas, 2013)
A rapid gas chromatography method using a HP Plot/Al2O3 column for the determination of thirteen compounds of LPG (Liquefied Petroleum Gas) standard (ethane, propane, propylene, iso-butane, n-butane, trans-2-butene, 1-butene, isobutylene, neo-pentane, cis-2-butene, iso-pentane, n-pentane, 1,3 butadiene) was developed. The LPG components were separated in about 8 min by gradient elution program and helium was used as a carrier gas at a flow rate of 5 mL min-1, The relative standard deviation (RSD) for the LPG standard concentration were found to range between 0.27-1.91 % . The method had been applied to the determination of the 10 LPG samples. The composition of analyzed samples have comply with the Indonesian LPG specification for each parameter (C2<0.8 % mol, C3+C4>97 % mol and C5+.<2.0 % mol).